1990
DOI: 10.1080/00268949008037233
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Response of Poly-(3-Methyl-Thiophene) to Various Anions in Aqueous Solutions

Abstract: Electrochemically formed films of poly-(3-methyl-thiophene), (PMeT), on platinum electrodes have been characterized by cyclic voltammetry in aqueous solutions containing KN03, KCIO,, KCI and K,SO,. An observed enhanced anodic current response for CVs in nitrate and perchlorate solutions compared to the responses for the other solutions, is believed to be due to the oxidizing power of the nitrate and perchlorate ions. The demonstrated effect may suggest the possibility of applying PMeT as a sensor for oxidizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 2 publications
0
10
2
Order By: Relevance
“…Unmodified CPs can respond readily to changes in their local environment. Unmodified CPs have been used to sense a great variety of analytes such as organic vapors, oxygen, nitrogen oxide gases, amines, hydrazines, pH, humidity, various ions, and cytochrome c . The reader interested in unmodified CPs as sensors should refer to recent reviews , and books .…”
Section: Unmodified Cps As Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unmodified CPs can respond readily to changes in their local environment. Unmodified CPs have been used to sense a great variety of analytes such as organic vapors, oxygen, nitrogen oxide gases, amines, hydrazines, pH, humidity, various ions, and cytochrome c . The reader interested in unmodified CPs as sensors should refer to recent reviews , and books .…”
Section: Unmodified Cps As Sensorsmentioning
confidence: 99%
“…Unmodified CPs can respond readily to changes in their local environment. Unmodified CPs have been used to sense a great variety of analytes such as organic vapors, [342][343][344][345] oxygen, 346 nitrogen oxide gases, 347 amines, 348 hydrazines, 349 pH, 350 humidity, 351 various ions, 352 and cytochrome c. 353 The reader interested in unmodified CPs as sensors should refer to recent reviews 354,355 and books. 356 Unmodified CPs tend to show very little specificity and are not useful as "stand alone" sensors but are very useful for arrays.…”
Section: Unmodified Cps As Sensorsmentioning
confidence: 99%
“…Significantly, polythiophenes can be straightforwardly synthesized using anodic electrodeposition techniques. There have been a number of studies conducted on electrochemically prepared polythiophene films for sensing applications Other than sensors, the high interest in polythiophene material is its potential for various applications such as smart coatings, organic light-emitting diodes, photovoltaics, and electrochromic windows. …”
Section: Introductionmentioning
confidence: 99%
“…But they did find a large effect of the dopant anion. In contrast, Sunde and co-workers [11] as well as Zhang and Dong [12] have shown that the voltammograms of PMT in aqueous electrolytes are strongly dependent on the types of anions present in the solution. Some work has been done on the effect of the electrolyte [13], but the effect of ion exchange on the electrochemical properties of PMT in aqueous solutions has not yet been investigated.…”
Section: Introductionmentioning
confidence: 91%